(untitled) (Jurnal Media Akuakultur Indonesia, 2021)
The Recirculation System is a method of raising fish in controlled containers to reuse used water after a physical and biological filtering process. One form of recirculation system is a multi layer filter. This research aims to determine water quality parameters and survival rates in the cultivation of the Banggai cardinal fish (P. kauderni) using a variation of a multi-layer filter recirculation system. This research activity was carried out for 1 month from February – March 2019 at the Cultivation Unit Laboratory of the Aquaculture Study Program-Pattimura University, Ambon. This research uses a recirculation container design with 2 system treatments and filter media used, namely dacron, activated charcoal, beach sand, bioball and mica ceramic. The data obtained was then analyzed using descriptive analysis, then the data was processed in Microsoft Office Excel 2010, presented in the form of tables and graphs. The results of this research show that the results of measuring the ammonia concentration obtained were that treatment B (Bioball, activated charcoal, dacron, and sand) could reduce ammonia more optimally with a concentration value in the last week of 0.3 mg/l and this treatment could maintain the survival of the fish. Banggai cardinal was around 66.67% better than the other treatments. It can be concluded that variations in the components of the multi-layer filter recirculation system in the treatment with a combination of bioball filters, activated charcoal, dacron and sand are able to reduce ammonia, as well as provide a better influence on water quality so as to increase the survival of the Banggai cardinal fish.